DNA methylation profiling in the clinic: applications and challenges - Heyn, Holger; Esteller, Manel (Nature reviews. Genetics, 2012)
Key Points Alterations in epigenetic marks — specifically DNA methylation — are an emerging biomarker that may be used in the decision-making process for disease diagnosis, prognosis and treatment, most notably in cancer, but there are examples in other diseases, such as type 1 diabetes. Alterations in epigenetic marks that are chosen as biomarkers must be carefully selected owing to the dynamic nature of these marks. These alterations may be detected in non-invasive tissues, such as serum, in addition to primary tissues and so may have advantages over genetic biomarkers. Glutathione S -transferase pi 1 ( GSTP1 ) is the best-studied example of an epigenetic biomarker for cancer diagnosis. However, additional candidates show a high potential for future clinical applications, although specificity of diagnosis is an issue, and combinatorial approaches analysing DNA methylation alterations at several genes may improve this. Single-gene approaches have identified epigenetic biomarkers that predict cancer recurrence and survival. Recently, high-resolution genome-wide technologies have shown the potential to improve this strategy with DNA methylation signatures of cancers showing high predictive capacity of disease prognosis. DNA methylation alterations may be used as biomarkers to predict response to chemotherapy strategies. O 6 -methylguanine DNA methyltransferase ( MGMT ) and breast cancer 1, early onset ( BRCA1 ) are examples of hypermethylated genes that predict a response to chemotherapy in cancer. Additional prognostic gene markers have already been identified and suggest DNA methylation profiling as a potent strategy to predict drug response. Recent advances in sequencing and array technologies, which are capable of screening DNA methylomes genome-wide at high-resolution, gave unexpected novel insights in cancer biology. They will be crucial for DNA methylation profiling and the identification of epigenetic biomarker for diagnosis, prognosis and prediction of drug response. Epigenetic alterations, notably in DNA hypermethylation, are emerging as consistent biomarkers for disease. Here, with a focus on cancer, the authors discuss the identification of these biomarkers and their use in disease diagnosis, prognosis and response to therapy. Knowledge of epigenetic alterations in disease is rapidly increasing owing to the development of genome-wide techniques for their identification. The ever-growing number of genes that show epigenetic alterations in disease emphasizes the crucial role of these epigenetic alterations — particularly DNA methylation — for future diagnosis, prognosis and prediction of response to therapies. This Review focuses on epigenetic profiling, which has started to be of clinical value in cancer and may in the future be extended to other diseases, such as neurological and autoimmune disorders.